2016
DOI: 10.1021/acs.jpcb.6b06628
|View full text |Cite
|
Sign up to set email alerts
|

Study of Electronic Structures and Pigment–Protein Interactions in the Reaction Center of Thermochromatium tepidum with a Dynamic Environment

Abstract: On the basis of the recently reported X-ray crystal structure of light-harvesting complex 1-reaction center (LH1-RC) complex from Thermochromatium tepidum, we investigate electronic structures and pigment-protein interactions in the RC complex from a theoretical perspective. Hybrid quantum-mechanics/molecular-mechanics methods in combination with molecular dynamics simulations are employed to study environmental effects on excitation energies of RC cofactors with the consideration of a dynamic environment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 137 publications
0
12
0
Order By: Relevance
“…As shown in Hamiltonian (4), explicit values of ω r q and g r q for individual bath modes are required in a proper description of the coupled exciton-phonon dynamics. Typically, these parameters are obtained by discretizing the bath spectral densities, which can be established from QM/MM calculations [53,71], or from fitting the fluorescence line-narrowing spectra [72,73] of the target system. It has been found that different methods can produce totally different spectral densities.…”
Section: Parameterization Of the Phonon Bathmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Hamiltonian (4), explicit values of ω r q and g r q for individual bath modes are required in a proper description of the coupled exciton-phonon dynamics. Typically, these parameters are obtained by discretizing the bath spectral densities, which can be established from QM/MM calculations [53,71], or from fitting the fluorescence line-narrowing spectra [72,73] of the target system. It has been found that different methods can produce totally different spectral densities.…”
Section: Parameterization Of the Phonon Bathmentioning
confidence: 99%
“…It has been found that different methods can produce totally different spectral densities. For instance, in spectral densities calculated by MD simulations of some photosynthetic systems, several high frequency (∼1670 cm −1 ) modes are found to couple strongly to the electronic transitions [53,71]. On the other hand, the spectral density obtained by fitting the fluorescence line-narrowing spectra of the B777 complex includes some low frequency modes strongly coupled to the excitons [73].…”
Section: Parameterization Of the Phonon Bathmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these transition charges and the molecular structures of the dimers, as given in Ref. [21], we then evaluated the interaction V using the Transition Charges from Electrostatic Potentials (TrEsp) method, which has been widely applied to accurately evaluate inter-molecular couplings [35][36][37][38] 1 . The angle α is also estimated directly from the given dimer structures (for details see section IV of the Supplementary Material.…”
Section: B Dimermentioning
confidence: 99%
“…The multiple excited states observed in the FMO complex are also due to the presence of different BChls in different local environments of the protein. While still debated, the possibility of existence of the long-lived quantum coherence also motivates to intensify the computational studies in different directions including the study of the excitation properties using different types of computational techniques [4,11,13,20,71,94,[132][133][134][135][136][137][138][139][140][141][142].…”
Section: Energetic and Spectroscopic Properties Using Dftmentioning
confidence: 99%